2020
DOI: 10.3168/jds.2019-16338
|View full text |Cite
|
Sign up to set email alerts
|

How benchmarking promotes farmer and veterinarian cooperation to improve calf welfare

Abstract: Little is known about the combination of factors that motivate changes in calf management on dairy farms. Providing information to farmers may help promote change, but it is unclear how this approach affects and is affected by the farmer's relationship with the advisors such as the herd veterinarian. The goal of this study was to understand how benchmarking measures related to calf immune development and growth affected farmer and veterinarian cooperation and influenced the farmer's view of the veterinarian as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…Participating in this study required that both farm managers and veterinarians set aside time to have a conversation around newborn calf care practices on their farm, something that was not done on a regular basis outside of the context of this study. Sumner et al (2020) found that having farmers sit down with their veterinarian led to conversations around calf management for the first time. Additionally, in many cases suggested changes to the SOP required veterinarian involvement (e.g., collecting blood samples).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participating in this study required that both farm managers and veterinarians set aside time to have a conversation around newborn calf care practices on their farm, something that was not done on a regular basis outside of the context of this study. Sumner et al (2020) found that having farmers sit down with their veterinarian led to conversations around calf management for the first time. Additionally, in many cases suggested changes to the SOP required veterinarian involvement (e.g., collecting blood samples).…”
Section: Discussionmentioning
confidence: 99%
“…Both knowledge (see Neu et al, 2011) and trustworthiness (see Strike, 2013) of external advisors may be significant in this development process; for instance, farmers may reject advice from experts who are not viewed as trustworthy (Garforth, 2015). In the dairy industry, veterinarians are viewed as trusted advisors by many dairy farmers (Sumner et al, 2020) and are frequently involved in developing health treatment protocols (Raymond et al, 2006). Boersema et al (2013) found that 10% of veterinarians sampled in the Netherlands provided preset treatment protocols to their clients.…”
Section: Introductionmentioning
confidence: 99%
“…Veterinarians are trusted advisors for dairy farmers (Stanley-Clarke, 2019;Sumner et al, 2020), and farmers respect their veterinarians (Golding et al, 2019). A trusted advisor has an explicit and implicit level of trust from the decision maker (Strike, 2013), and these individuals are believed to provide the highest quality information (Neu et al, 2011).…”
Section: The Veterinarian As An Advisormentioning
confidence: 99%
“…These "bobby" calves are particularly vulnerable due to the very young age at which they are removed from their dam, handled, and transported prior to slaughter [1,4]. Given that welfare inputs are inextricably linked to economic outputs [5][6][7], and the economic value of bobby calves is considered nominal, the low prioritization of young calves raises important concerns for their welfare [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The New Zealand Veterinary Association (NZVA) has emphasized the necessity of targeted interventions to improve calf welfare, affirming that the Act must not only protect cattle from overt cruelty, but also protect their physical and psychological health and welfare [14,15]. Given that veterinarians are considered educators [7], advisors [16,17], influencers [7,[18][19][20], and informed assessors of animal welfare [21], the perceptions of veterinarians have direct implications for the level of welfare protection afforded to calves in practice [22][23][24].…”
Section: Introductionmentioning
confidence: 99%